Assessment Types of Domestic Violence Among Iraqi Pregnant Women - Khairi, suhad; Abbas, Ekbal (Iraqi National Journal of Nursing Specialties, 2007)
Objective : A descriptive analytical study was conducted on pregnant women who face domesticviolence and receive antenatal services from obstetric wards ikou^V Ctemal ^4M^vrAd\vQ^Ms> "&Baghdad city, to identify the types of domestic violence on pregnant woman.Methodology : A purposive sample of one hundred pregnant women with domestic violence wasselected. Data were collected through questionnaire, the period extended from the 20th Feb to the 3rdMay 2006. Descriptive and inferential statistical procedures were used to analyze the data.Results : The result of the study showed that the highest percentage (26%) of the study sample theirage ranges from (30 - 34) years, most of them were housewife with low socioeconomic status, twothird of the study sample were with low educational level. The number of parity ranged between (2-5)child and more.The study findings revealed that the majority of study sample suffer from hitting, criticizing andshouting during their daily life, threaten to be left, keep control on her income and force her for sex. Thepsychological domestic violence was in higher level of relative sufficiency, the physical domesticviolence was in moderate level of relative sufficiency, while social and sexual abuse considered lowlevel of relative sufficiency.Recommendation : The study recommended routine screening for women for any type of domesticviolence during fertile age. Addressing domestic violence in medical and nursing curriculum, usingmass media, availability of health services and support enhance cooperation between social agencies"justice and police with enforcing laws and research for the promotion and protecting women's rights.